Faktor-Faktor yang Mempengaruhi Underprice Penawaran Saham Perdana di Indonesia - Hartanto Hartanto (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
The characteristics of an Initial Public Offering (IPO) is an important factor for several parties in achieving their goals, for example, for companies (which release the shares) will have a projection of the capital to be obtained, as well as for underwriters and investors to maximize their profits. Lack of knowledge of the character of the IPO, can cause problems, especially the potential loss to the several parties. This study aims to explore the character of IPO in Indonesia, especially the occurrence of Underprice and what are the factors that influence it. This study uses prospectus data of companies that conduct IPOs on the JSX, data library and websites that have the necessary data, the period 1995 to 2001. The results show that the Underprice phenomenon does indeed occur on IPOs on the JSX and most of the variables tested have an influence underprice occurrence. This study provides several suggestions including the need for the addition of more various variable.